Circular RNA circHIPK3 promotes breast cancer progression via sponging MiR-326. Issue 13 (3rd July 2021) - Luo, Na; Liu, Shiqin; Li, Xin; Hu, Yu; Zhang, Kejing
ABSTRACT: Background : This study investigated the potential molecular mechanism of circular RNA HIPK3 (circHIPK3) in breast cancer (BCa). Methods : BCa cells were transfected with miR-326 mimic, miR-326 inhibitor, circHIPK3, sicircHIPK3. The expressions of circHIPK3 and miR-326 in BCa tissues and BCa cell lines were determined by RT-qPCR. Cell viability, colony formation, migration, invasion, and apoptosis of the cells were detected by CCK-8 and colony formation, wound-healing, transwell and flow cytometric assays, respectively. The relationship between circHIPK3 and miR-326 was analyzed and confirmed by circInteractome, dual-luciferase reporter, RT-qPCR, Pearson's correlation assays. Western blot and RT-qPCR were performed to determine the expressions of apoptosis-related molecules (Bcl-2, Bax, and cleaved Caspase-3) and EMT-related molecules (E-cadherin, N-cadherin, and Vimentin) in the BCa cells and tumor tissues. The tumor growth in mice was examined in a xenograft tumor model in which Ki-67 expression was determined by immunohistochemistry (IHC). Results : In BCa, the expression of circHIPK3 was up-regulated and that of miR-326 was down-regulated. CircHIPK3 knockdown inhibited the cell proliferation, invasion, and migration. MiR-326 was the direct target of circHIPK3, and was inversely correlated with circHIPK3 expression. CircHIPK3 overexpression promoted proliferation, migration, invasion, apoptosis resistance, and tumor growth and up-regulated Ki-67 expression, at the same time, the expressions of Bcl-2, N-cadherin, Vimentin were up-regulated, and those of Bax, cleaved Caspase-3 and E-cadherin were inhibited. These above expressions were partially reversed by miR-326 overexpression. Conclusion : CircHIPK3 sponges miR-326 to promote BCa growth and metastasis. The current findings provide a novel therapeutic target for treating BCa.